PENGARUH VARIABEL KEUANGAN PERUSAHAAN (RETURN ON ASSET, EARNING PER SHARE, CURRENT RATIO, DAN FINANCIAL LEVERAGE) TERHADAP UNDERPRICING - Maryoto Maryoto; Salamatun Asakdiyah (Jurnal Fokus Manajemen Bisnis, 2014)
This research wa carried out on companies that do the Initial Public Offering (IPO) in the period 2008-2009. With a population of 31 companies and get a sample of 27 companies with the technique of sampling using purposive sampling. In this study tested the hypothesis by using multiple regression and t test. After doing an analysis of 27 companies in initial public offering in 2008 until 2009 are listed in Indonesia Stock Exchange, obtained the results of the calculation of the coefficient of determination (R2) obtained a value 0f 0.170 is in a position of positive mean return on assets (ROA), earning per share (EPS), current ratio (CR), and financial leverage (FL) 1.7% to explain underpricing. Thus 98.3% underpricing is explained by other variables not examined in this study. By using the t test for variable return on assets (ROA), earnings per share (EPS), current ratio (CR), and financial leverage (FL) had no significant influence on underpricing with the test results significantly greater value than the alpha (5%).